An Examination of al Imam al Alusi’s Contributions to Selected Theological Issues in His Tafsir - Suraju, Saheed Badmus (FIKRAH, 2021)
Theology as a branch of knowledge in Islamic studies,it’s still a debate among Muslims.Especially in contemporary times. This article provides a resume of al-Imam al-Alusi's contribution, as commentator, to the theological discussions in his Magnum Opus: Ruhul-Maani. To achieve this, this paper examines his views on several theological issues selected in his attempt to interpret the verses of the Qur'an with the main aim of discovering the quality and suitability of his arguments and their conformity with the basic principles and sources of Islam. This paper aims to share information about its stance and provide clarification if needed. The findings reveal that al-Imam al-Alusi's theological discussion includes the views of the major Islamic sects; Sunnis, Shi'ites, Mu'tazilites, Ash'arites, among others and brought their own opinions. It is also established that theological differences arise from philosophical thought in defense of individual sects. It was also revealed that the divergence did not affect the fundamentals of Islamic theology.